2008
DOI: 10.1099/vir.0.83621-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of viral silencing suppressors on tobacco ringspot virus infection in two Nicotiana species

Abstract: This study investigated the effects of silencing suppressors derived from six different viruses (P1, P19, P25, HcPro, AC2 and 2b), expressed in transgenic Nicotiana tabacum and Nicotiana benthamiana plants, on the infection pattern of tobacco ringspot virus (TRSV) potato calico strain. In N. benthamiana, this virus produced an initial infection with severe systemic symptoms, but the infection was strongly reduced within a few weeks as the plant recovered from the infection. P25 and HcPro silencing suppressors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 41 publications
3
31
1
Order By: Relevance
“…In contrast, Tomato black ring virus (TBRV, a subgroup B Nepovirus) was not detectable in asymptomatic leaves of Nicotiana clevelandii (Ratcliff et al 1997). Similarly, TRSV potato calico strain did not accumulate in the uppermost asymptomatic leaf of N. benthamiana at 40 dpi (Siddiqui et al 2008). In our study, TRSV-Ib1 continuously infected the asymptomatic leaves of N. benthamiana at 20 dpi, whereas TRSV-Ib1 was not detected in the asymptomatic leaves of tobacco plants.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…In contrast, Tomato black ring virus (TBRV, a subgroup B Nepovirus) was not detectable in asymptomatic leaves of Nicotiana clevelandii (Ratcliff et al 1997). Similarly, TRSV potato calico strain did not accumulate in the uppermost asymptomatic leaf of N. benthamiana at 40 dpi (Siddiqui et al 2008). In our study, TRSV-Ib1 continuously infected the asymptomatic leaves of N. benthamiana at 20 dpi, whereas TRSV-Ib1 was not detected in the asymptomatic leaves of tobacco plants.…”
contrasting
confidence: 56%
“…In addition, differences were reported between leaves and roots in RNA silencing activity against the virus (Andika et al 2005;Rahim et al 2007). Recently, Siddiqui et al (2008) reported that some silencing suppressors affected the temperature-dependent infection pattern of the TRSV potato calico strain in transgenic tobacco plants, although the authors did not describe the effect of silencing suppressors on the recovery phenotype of TRSV-infected tobacco plants. To elucidate the mechanism of the differences in TRSV infection kinetics among shoot meristem, root meristem and un-inoculated upper leaves of the tobacco plant, involvement of RNA silencing in the recovery of RAM and un-inoculated upper leaves from TRSV infection will first need to be verified.…”
mentioning
confidence: 97%
“…This was most apparent with 3-1 and 4-1. The explanation may be differences in plant RNA silencing activity; at lower temperature the host defence silencing mechanism appears to be less effective (Chellappan et al, 2005;Jovel et al, 2007;Qu et al, 2005;Siddiqui et al, 2008), allowing a proportionately greater increase in virus replication and/or number of cells infected by the challenging virus.…”
Section: Determinants Of Altmv Pathogenicitymentioning
confidence: 99%
“…Most involve the elaboration of proteins that recognize and inactivate elements of the silencing pathway (Siddiqui et al 2008). Over 50 such virus-encoded silencing suppressors have been discovered (Burgyan 2011).…”
Section: Silencing Suppressionmentioning
confidence: 99%